Genome-enabled and phenotypic selection of alfalfa for widely-diversified cropping environments - Annicchiarico, Paolo; Nazzicari, Nelson; Bouizgaren, Abdelaziz; Hayek, Taoufik; Laouar, Meriem; Cornacchione, Monica; Basigalup, Daniel Horacio; Brummer, Edward Charles; Pecetti, Luciano (2018)
The decrease of rainfall amount due to climate change, and the reduction of irrigation water caused by growing water demand for non-agricultural uses, emphasize the importance of breeding novel alfalfa varieties that are more tolerant to drought under rain-fed cropping or modest supplemental irrigation, and more tolerant to salt to exploit low-quality, saline irrigation water. A sharp need for such improved germplasm is emerging in the Mediterranean basin, where alfalfa plays a key role for forage production. Drought-tolerant cultivars are needed also elsewhere, for example in Argentina, where they could allow to expand westward the alfalfa rain-fed cropping. Alfalfa typically features very low rates of genetic yield gain (Annicchiarico et al. 2015a), urging the development of cost-efficient marker-based selection. The multi-site yield testing of alfalfa varieties and landraces across countries of the western Mediterranean basin revealed outstanding genotype × environment (GE) interaction of cross-over type associated with three major types of target environments: i) rain-fed or irrigated environments featuring limited spring-summer water available and low salinity, ii) salt-stress environments, and iii) moisture-favorable environments (Annicchiarico et al. 2011). Eco-physiological research identified various mechanisms that contribute to specific-adaptation responses (Annicchiarico et al. 2013). Moderately wide cultivar adaptation may be desirable, given the wide year-to-year climatic variation of sites in this region. A Mediterranean reference population of alfalfa was developed from elite germplasm within the ERA-Net project REFORMA. A genotype training set was sorted out from it, to verify the ability of genomic selection (Heffner et al. 2009) to predict breeding values for biomass yield across a range of widely-diversified cropping environments. Genotype breeding values were estimated according to responses of their half-sib progenies, as required by the crop outbred system (Annicchiarico et al. 2015a). The genotyping of parent genotypes was carried out by Genotyping-by-Sequencing (Elshire et al. 2011) after optimizing for alfalfa some elements of its protocol (Annicchiarico et al. 2017). Concurrently, the project verified the ability of managed-stress environments of Italy to predict genotype yield responses in distant agricultural environments, following earlier work showing good ability to predict cultivar responses across agricultural environments of Italy (Annicchiarico and Piano 2005). This study aimed to provide an initial assessment of the ability of genomic selection to predict breeding values in each cropping environment and across stress environments, on the basis of preliminary yield data and GBS-generated data.